Storage-associated genes and reserves accumulation in soybean cultivars differing in physiological strategies for attaining high seed protein concentration - Poeta, Florencia Belen (2017)
High seed protein concentration (HP) in soybeans [Glycine max (L.) Merr.] is attained by increases in protein content in large seed genotypes (HP large seed) or by reductions in oil and carbohydrates contents in small seed genotypes (HP small seed). We hypothesized that these alternative strategies impact seed development, component accumulation, and gene expression differently. We compared a standard protein commercial genotype with two HP genotypes having contrasting seed size. The HP large seed genotype exhibited the fastest rate and longest period of seed growth and reserves accumulation compared with the HP small genotype. Seed development of these contrasting genotypes was normalized using a moisture depletion framework. Expression levels of some of the genes involved in protein and oil synthesis were lower in the HP small seed genotype compared with the other genotypes. No difference in gene expression was observed between the commercial and the HP large seed genotypes, suggesting a role for assimilate supply controlling high protein concentration based on this strategy. Our results indicate that seed development and gene expression are not necessarily associated with high seed protein concentration per se; a better understanding of seed composition requires acknowledging the contrasting strategies, in terms of seed size, to attain high seed protein concentration.